Insulin and the kidneys: a contemporary view on the molecular basis - Daza-Arnedo, Rodrigo; Rico-Fontalvo, Jorge; Aroca-Martínez, Gustavo; Rodríguez-Yanez, Tomás; Martínez-Ávila, María Cristina; Almanza-Hurtado, Amilkar; Cardona-Blanco, María; Henao-Velásquez, Carlos; Fernández-Franco, Jorge; Unigarro-Palacios, Mario; Osorio-Restrepo, Carolina; Uparella-Gulfo, Isabella (Frontiers in Nephrology, 2023)
Insulin is a hormone that is composed of 51 amino acids and structurally organized as a hexamer comprising three heterodimers. Insulin is the central hormone involved in the control of glucose and lipid metabolism, aiding in processes such as body homeostasis and cell growth. Insulin is synthesized as a large preprohormone and has a leader sequence or signal peptide that appears to be responsible for transport to the endoplasmic reticulum membranes. The interaction of insulin with the kidneys is a dynamic and multicenter process, as it acts in multiple sites throughout the nephron. Insulin acts on a range of tissues, from the glomerulus to the renal tubule, by modulating different functions such as glomerular filtration, gluconeogenesis, natriuresis, glucose uptake, regulation of ion transport, and the prevention of apoptosis. On the other hand, there is sufficient evidence showing the insulin receptor’s involvement in renal functions and its responsibility for the regulation of glucose homeostasis, which enables us to understand its contribution to the insulin resistance phenomenon and its association with the progression of diabetic kidney disease.